Subjective experiences of an acceptance and mindfulness-based group intervention (Feel-Good-Group) in young people with early psychosis - von Hardenberg, Laura; Leopold, Karolina; Pfennig, Andrea; Kuhn, Céline; Kallenbach, Michèle; Aliakbari, Navid; Mehl, Stephanie; Bechdolf, Andreas (Frontiers in Psychiatry, 2024)
Background: Mindfulness-based interventions are promising psychological treatment approaches that may have more substantial long-lasting intervention effects than cognitive behavioral therapy when treating individuals with early psychosis. A pilot study analyzed mindfulness-based inpatient group therapy's feasibility and potential efficacy (Feel-Good).Objective: This paper explores the subjective experiences of participants in the Feel-Good inpatient therapy group to gain insight into the possible changes brought about by the mindfulness-based intervention.Methods: A semi-structured change interview was used to examine the experience of ten participants who participated in the Feel-Good intervention and the additional qualitative assessment. The interviews were conducted 16 weeks after the Feel-Good group ended (16-week Follow-Up).Interviews were transcribed verbatim and analyzed using thematic analysis.Results: The analysis generated five themes-one about personal changes brought about by the Feel-Good group, three about the group therapy experience, and one about wishes/modification suggestions to change and improve the Feel-Good group. The findings suggested that the Feel-Good group was perceived as very helpful, leading to numerous changes in one's overall well-being and relation to emotions. However, patients recommended a more directive therapeutic style and reduced time required for study assessments.Gathering qualitative insight from participants on the Feel-Good intervention revealed meaningful insight into patients' experience of change processes. In addition, participant suggestions help to improve the intervention and study design to increase therapy attendance rates and treatment satisfaction, potentially increasing treatment effectiveness in the future.